2016
DOI: 10.3847/0004-637x/819/1/81
|View full text |Cite
|
Sign up to set email alerts
|

LYMAN CONTINUUM ESCAPE FRACTION OF STAR-FORMING DWARF GALAXIES AT z ∼ 1

Abstract: To date, no direct detection of Lyman continuum emission has been measured for intermediate-redshift (z 1) star-forming galaxies. We combine Hubble Space Telescope grism spectroscopy with GALEX UV and groundbased optical imaging to extend the search for escaping Lyman continuum to a large (∼600) sample ofz 1 low-, moderately star-forming (Y  10  M yr −1 ) galaxies selected initially on Hα emission. The characteristic escape fraction of LyC from star-forming galaxies (SFGs) that populate this parameter space … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
97
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 103 publications
17
97
0
Order By: Relevance
“…Studies with the HUT (Leitherer et al 1995) and the HST SBC (e.g., Malkan et al 2003;Siana et al 2010) do not detect escaping LyC. Large archival studies of LyC emission from SFGs (Cowie et al 2009) and Hα-selected emission line galaxies (Rutkowski et al 2016) have generally reported non-detections, likely indicating that the strong star formation may be conducive to LyC escape, but does not guarantee it. Until recently, few LyC leakers were known; local starbursts Tol 0440-381, Tol 1247-232, Mrk 54, and Haro11 (e.g., Leitherer et al 2016;Puschnig et al 2016) and, at z2, fewer than ∼10, UV-selected SFGs (e.g., de Mostardi et al 2016;Smith et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Studies with the HUT (Leitherer et al 1995) and the HST SBC (e.g., Malkan et al 2003;Siana et al 2010) do not detect escaping LyC. Large archival studies of LyC emission from SFGs (Cowie et al 2009) and Hα-selected emission line galaxies (Rutkowski et al 2016) have generally reported non-detections, likely indicating that the strong star formation may be conducive to LyC escape, but does not guarantee it. Until recently, few LyC leakers were known; local starbursts Tol 0440-381, Tol 1247-232, Mrk 54, and Haro11 (e.g., Leitherer et al 2016;Puschnig et al 2016) and, at z2, fewer than ∼10, UV-selected SFGs (e.g., de Mostardi et al 2016;Smith et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…The two effects, however, may be negligible for our low-mass galaxies. The Lyman continuum escape fraction is less than 2% for galaxies at z ∼ 1 (Siana et al 2007(Siana et al , 2010Rutkowski et al 2016). And the dust absorption would preferentially affect massive (and hence dustier) galaxies rather than low-mass systems.…”
Section: Effects Of Dust Extinction Correctionmentioning
confidence: 99%
“…On the other hand, recent estimates of the Lyman continuum escape fraction for low mass star-forming galaxies at z ∼ 1 based on HST grism spectroscopy plus GALEX FUV indicate escape fractions of less than 2% (Rutkowski et al 2016), which would not be sufficient to illuminate external gas.…”
Section: Associated H I Gasmentioning
confidence: 99%